Distribution of deep-sea benthos communities around Iceland: their biodiversity and impact factors - Bylgja Sif Jónsdóttir 1993- (2024)
Deep-sea ecosystems are the most extensive on earth and could host great proportion of undiscovered biodiversity. With increasing demand for fisheries products and utilization of the deep-sea environment, those ecosystems are under threat. Sustainable fishing and protection of vulnerable marine ecosystems (VMEs) have attempted to ameliorate these threats and have led to growing demand for information on the effects of fishing and its impacts on marine ecosystems globally. The Marine and Freshwater Research Institute (MFRI) of Iceland has conducted annual Autumn groundfish surveys in deep-sea (144-1340 m) areas since 1996. In 2016-2018 benthic researchers onboard survey vessels collected and recorded benthic bycatch. The benthos consists of animals living as epifauna on the seafloor or as infauna burrowed within it. Deep-sea benthos are well adapted to the cold and dark environments of their habitat but tend to be fragile, slow growing and long-lived, making them vulnerable to fishing pressure. The aim of the study was to explore the distribution and biodiversity of the deep-sea benthos and their potential environmental impact factors. The Icelandic Economic Exclusion Zone was divided into four ecoregions and the seafloor categorized into ten different geomorphology types. Both showed a strong influence on the measurable species abundance. The current study provides valuable insight into the complex and diverse benthic ecosystems of the deep-sea around Iceland, creating a great baseline for future research. Knowledge of the biodiversity and distribution of marine species affected by anthropogenic pressure is vital to improve management and conservation of marine biodiversity and of VMEs. Djúpsjávarvistkerfin eru þau umfangsmestu á jörðinni og eru talin hýsa stóran hluta af líffræðilegri fjölbreytni sem enn á eftir að lýsa. Með aukinni eftirspurn eftir sjávarafurðum on nýtingu djúpsjávarins er þessum mikilvægu og oft lítt þekktum vistkerfum ógnað. Sjálfbærar veiðar og verndun viðkvæmra vistkerfa sem finnast í ...